World book encyclopedia Vol. 2 B / Marie Alice Anderson - Anderson, Marie Alice (2001)
A baby's development before birth, growth and development, development of motor skills, baby care, providing proper environment, bathing the baby, health care and safety, baby boom generation, the new Babylonian empire, the ruins of Babylon, language and literature, history, the Sumerians, the Semites, his works, bachelor's-button, additional resources, the importance of bacteria, the life of bacteria, where bacteria live.